Blackbird - Kapurch, Katie; Smith, Jon Marc (Penn State University Press, 2025)
From the beginning, the Beatles acknowledged in interviews their debt to Black music, apparent in their covers of and written original songs inspired by Chuck Berry, Little Richard, Fats Domino, the Shirelles, and other giants of R&B. Blackbird goes deeper, appreciating unacknowledged forerunners, as well as Black artists whose interpretations keep the Beatles in play. Drawing on interviews with Black musicians and using the song “Blackbird” as a touchstone, Katie Kapurch and Jon Marc Smith tell a new history. They present unheard stories and resituate old ones, offering the phrase “transatlantic flight” to characterize a back-and-forth dialogue shaped by Black musicians in the United States and elsewhere, including Liverpool. Kapurch and Smith find a lineage that reaches back to the very origins of American popular music, one that involves the original twentieth-century blackbird, Florence Mills, and the King of the Twelve String, Lead Belly. Continuing the circular flight path with Nina Simone, Billy Preston, Jimi Hendrix, Aretha Franklin, Sylvester, and others, the authors take readers into the twenty-first century, when Black artists like Bettye LaVette harness the Beatles for today. Detailed, thoughtful, and revelatory, Blackbird explores musical and storytelling legacies full of rich but contested symbolism. Appealing to those interested in developing a deep understanding of the evolution of popular music, this book promises that you’ll never hear “Blackbird”—and the Beatles—the same way again.